O dilema cosmopolita versus nacional nas vanguardas latino-americanas: uma comparação entre a revista Martín Fierro e a Revista de Antropofagia (1924-1929) - Helaine Nolasco Queiroz (2018)
This thesis aimes to elaborate a comparative analysis between two avantgarde magazines that circulated in 1920 in Brazil and Argentina: Revista de Antropofagia and Martín Fierro. We try to examinate, in both periodicals, how it is developed a tension between a cosmopolite orientation and the trial of identifying and promoting the most authentic characteristics of each one of the nations. The magazines are examined in their paratextual characteristics, writing an analysis in with text, paratext and context are studied together to understand the proposals at the same time nationalistic and cosmopolites from the avant-garde magazines.